Black Panther. A nation under our feet, Book 1 - Coates, Ta-Nehisi (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment , LLC., 2016)
"T'Challa confronts a dramatic upheaval in Wakanda that will make leading the African nation tougher than ever before. When a superhuman terrorist group calling itself The People sparks a violent uprising, the land famed for its incredible technology and proud warrior traditions will be thrown into turmoil. As suicide bombers terrorize the population, T'Challa struggles to unite his citizens, and a familiar villain steps out of the shadows. If Wakanda is to survive, it must adapt--but can its monarch, one in a long line of Black Panthers, survive the necessary change? Heavy lies the head that wears the cowl!"--pg.4 of cover.